Synthesis and characterization of Co/CNTs catalysts prepared by strong electrostatic adsorption (SEA) method - Akbarzadeh, O. (Trans Tech Publications Ltd, 2014)
Strong Electrostatic Adsorption (SEA) is an effective method to synthesize and introduce Cobalt nano particles on Carbon Nanotubes (CNTs) support. Point of zero charge (PZC) of CNTs and optimum pH, the cobalt uptake versus different pH were investigated. By using the range of characterization methods such as TEM, FESEM and TPR catalyst prepared was studied. TEM and FESEM images indicate well-dispersed cobalt particles on the CNTs support. TPR was proven reduction peak at high temperature (530oC) indicating strong interaction between Cobalt and CNTs support. SEA showed the desired method in preparing supported cobalt catalysts. Â© 2014 Trans Tech Publications, Switzerland.